A report of the medical team activity at the 2009 Special Olympics GB. Issue 2 (2nd March 2011) - Wheeler, Patrick C; Williamson, Tim; Stephens, Catherine; Ferguson, Mike
Abstract : Objective: To quantify and categorise medical workload from the 2009 Special Olympics GB (SOL GB) which involved 2500 athletes with learning disabilities across 21 different sports supported by nearly 9000 family members, volunteers and staff over a 7-day period. Design and participants: Prospective survey of all medical contacts that took place at the 2009 SOL GB with subsequent analysis of consultation rates, medical problems and medical activity. Results: 581 medical consultations occurred during the 2009 SOL GB, with 95% of these for athletes. The majority of the athlete consultations were for musculoskeletal disorders, followed by skin wound care. Most athletes were judged fit to participate following their consultation. Conclusion: A large multisport event for athletes with learning disabilities carries a significant medical workload that has not been studied previously, with different sports having different individual risks and demands. The vast majority of consultations are for systemically well athletes that can be managed locally without necessity for hospital admission. This study identifies the quantity and nature of medical consultations undertaken during this event in an attempt to inform planning for future events.